Clinical characteristics and prognosis of patients with idiopathic membranous nephropathy with kidney tubulointerstitial damage - Mengyao Sun; Ping Li; Jianwei Dong; Zhuo Li; Chaofan Li; Shasha Zhang; Bing Chen (Renal Failure)
Background To investigate the clinical and kidney pathological features and prognosis of idiopathic membranous nephropathy (IMN) with kidney tubulointerstitial damage (TID).Methods Based on the presence or absence of kidney TID by kidney biopsy, 300 patients diagnosed with IMN were categorized into non-TID (TID−) and tubulointerstitial injury (TID+) groups. The clinical and pathological data were analyzed retrospectively. All patients were followed up for 6–24 months after treatment with glucocorticoids (GCs) combined with cyclophosphamide or GCs combined with calcineurin inhibitors (CNIs) to observe treatment effects on patient prognosis.Results The patients in the TID + group were older and more likely to be male. The 24-h urine protein, blood urea nitrogen, serum creatinine, cystatin C, β2-microglobulin, and antiphospholipase A2 receptor antibody levels were higher than those in the TID − group and the pathological manifestations were more severe. After 1 year of follow-up, the overall response rate (complete response + partial response) in the TID + group was lower (66.67% vs. 80.89%, p = .022) than in the other. After combined GC and CNI therapy, the complete remission rate in the TID + group was significantly lower than that in the TID − group (13.79% vs. 35.46%, p = .022). The 24-h urine protein level was an independent risk factor for worsening kidney condition (p = .038).Conclusion Patients with IMN with TID have more severe clinical manifestations and pathological damage and lower remission rates. IMN with TID is a risk factor for worsening kidney condition; however, it is not an independent risk factor.